Mapping the Evidence-base of Adolescent and Adult Vaccination in Africa: A slow but growing trend - Haddison, Eposi C.; Machingaidze, Shingai; Wiysonge, Charles S.; Kagina, Benjamin M (J Vaccines Immunol, 2019)
Historically, immunisation has largely focused on children. There is an increased realisation that optimal control of vaccine preventable diseases (VPDs) requires an extension of immunisation to adolescents and adults. Research is vital to guide the extension of adolescent and adult immunisation without interference with the childhood immunisation programmes. We therefore conducted a study assessing the types and quality of available research on adolescent and adult immunisation in Africa from 2011 to 2019.
Keywords: Mapping; adolescent and adult vaccination